2022
DOI: 10.1371/journal.pntd.0010578
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of intralesional sodium stibogluconate for the treatment of localized cutaneous leishmaniasis at Boru Meda general hospital, Amhara, Ethiopia: Pragmatic trial

Abstract: Background Cutaneous leishmaniasis (CL) is generally caused by Leishmania aethiopica in Ethiopia, and is relatively hard to treat. Sodium stibogluconate (SSG) is the only routinely and widely available antileishmanial treatment, and can be used systemically for severe lesions and locally for smaller lesions. There is limited data on the effectiveness of intralesional (IL) SSG for localized CL in Ethiopia and therefore good data is necessary to improve our understanding of the effectiveness of the treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(30 citation statements)
references
References 24 publications
(45 reference statements)
1
26
0
Order By: Relevance
“…Our study has provided evidence that heavy parasite loads observed during histological examinations predict a poor response to SSG and longer healing times. Similar observations have been reported in localized CL due to L. aethiopica , where SSS with lower parasite numbers were associated with a higher chance of cure 25 . The response to effective treatment is typically expected to be higher and faster during the early stages of infection, when parasites are abundant and easier for the drug to reach, in contrast to chronic and relapsing forms of CL, which are usually associated with low parasite loads and fibrotic tissue reactions.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Our study has provided evidence that heavy parasite loads observed during histological examinations predict a poor response to SSG and longer healing times. Similar observations have been reported in localized CL due to L. aethiopica , where SSS with lower parasite numbers were associated with a higher chance of cure 25 . The response to effective treatment is typically expected to be higher and faster during the early stages of infection, when parasites are abundant and easier for the drug to reach, in contrast to chronic and relapsing forms of CL, which are usually associated with low parasite loads and fibrotic tissue reactions.…”
Section: Discussionsupporting
confidence: 75%
“…Oliveira et al., conducting a study in a similar setting, reported that the size of the ulcer at the first medical visit correlated with healing time, 29 while treatment failure was more likely when referred 5 months after the onset of lesions due to L. tropica 30 . The addition of other treatment modalities, such as cryotherapy, as we and others have reported, is often a clinical decision based on features such as the type of lesion 25 . Further comprehensive studies are required to investigate if such combination therapies, which apparently improve the efficacy of treatment, have similar clinicopathological associations.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…aethiopica [ 17 , 18 ]. Among LCL cases treated with six cycles of intralesional-SSG v (IL-SSG v ), a higher chance of cure was positively associated with being male, increasing age and SSS grade +1 and +2 [ 18 ]. With 28 days of oral miltefosine treatment, MCL cases showed lower odds of relapse on day 180 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%